A Comparative Study on the Perception Level of the Services Offered by LIC and ICICI Prudential - Keerthi, Pa; Vijayalakshmi, R. (Indian Journal of Marketing, 2009)
Insurance is a service industry and the main focus is on the efficient and effective delivery of services to the policyholders. The most important factors in the insurance industry are security of the amount insured and customer satisfaction. This can be achieved by delivering quality service for it being the pivotal element that has its reflection on customer retention, loyalty and winning the hearts of new customers and ultimately enhances an insurance company to achieve its corporate goal of more profit, increment in market value and share. Analyzing the levels of expectation and perception would reveal a birds eye view of the exact delivery of service and helps organizations to focus on the key areas. Thus customer satisfaction is the end result of customer expectations and perceptions of the services offered by the life insurance companies. This survey focuses to find out the expectation level and compares the perception level of services offered by LIC and ICICI prudential.